Comparison between Lacunary and Saturated Keggin Polyoxometalates as Steel Corrosion Inhibitors in Chloride Solution: Contribution of the Lacuna in the Inhibition Mechanism. Issue 32 (27th August 2020) - Romaric Wamba Tchio, Odilon; Pengou, Martin; Baumier, Cédric; Franger, Sylvain; Teillout, Anne‐Lucie; Martyr Mbomekallé, Israël; De Oliveira, Pedro; Péguy Nanseu‐Njiki, Charles; Ngameni, Emmanuel
Abstract: The effect of two lacunary Keggin polyoxometalates (K7 [PW11 O39 ].14H2 O and K9 [AlW11 O39 ].15H2 O) on the corrosion inhibition of XC38 steel in 0.1 M NaCl was investigated. Electrochemical methods (polarization curves and electrochemical impedance spectroscopy) showed that the presence of controlled amounts of these compounds improved protection of the steel against corrosion. These results were supported by surface analysis, where only a minor amount of rust was produced on metal surface in the presence of polyoxometalates (POMs). The lacunary POMs were more efficient compared to their saturated species, highlighting the key role played by the lacuna on the inhibition process. Efficiency of POMs (both saturated and lacunary) was explained by their ability to increase the Fe(II)/Fe(III) molar ratio in greenish protective oxide layer formed upon steel oxidation. The mechanism proposed clearly explains the higher efficiency observed with lacunary POMs, in relation to their ability to react with free Fe(III) to yield a substituted structure. Abstract : Used as steel corrosion inhibitors in NaCl, Keggin lacunary POMs (PW11 and AlW11) favor the formation and reinforcement of a greenish protective oxide layer rich in Fe(II) on the steel surface. These POMs thus provide a better corrosion inhibition compare to their saturated equivalents (PW12 and AlW12) used in the same experimental conditions. The in situ formation of iron‐substituted POMs at the steel‐solution interface is an important step in the corrosion inhibition process in the presence of lacunary POMs.